2005
DOI: 10.1175/jhm432.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Precipitation Properties Associated with the Monsoon over Palau in the Western Pacific

Abstract: In this study, the authors focused on the seasonal variations of precipitation properties over the western Pacific, particularly those associated with the wind direction of the monsoon. An observational project over Peleliu Island in the Republic of Palau was carried out, and data on precipitation, equivalent cloud amount, and precipitable water were collected from 28 June 2001 to 30 April 2002. First, the monsoon season over Palau was defined as a period with 850-hPa zonal-wind sounding data with sustained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Southeasterly wind becomes strong over the Banda Sea and Arafura Sea from June in climatology. It is associated with the seasonal wind over the western North Pacific monsoon including Koror of Palau (Murakami and Matsumoto 1994;Kubota et al 2005). Strong wind area spreads to north of the equator through the Molocca Strait and Halmahera Sea and turns southwesterly.…”
Section: Possible Mechanisms For Interannual Variabilitymentioning
confidence: 99%
“…Southeasterly wind becomes strong over the Banda Sea and Arafura Sea from June in climatology. It is associated with the seasonal wind over the western North Pacific monsoon including Koror of Palau (Murakami and Matsumoto 1994;Kubota et al 2005). Strong wind area spreads to north of the equator through the Molocca Strait and Halmahera Sea and turns southwesterly.…”
Section: Possible Mechanisms For Interannual Variabilitymentioning
confidence: 99%
“…Some studies (Tanaka 1992;Lau and Yang 1997;Wang and LinHo 2002) used satellite data of outgoing longwave radiation (OLR) to define an index of convective activity. Kubota et al (2005) used satellite-based wind data to identify the change of wind direction to define the monsoon onset. These studies determined that the Philippine summer monsoon starts around May to early June with the arrival of moist low-level westerly wind and the start of active convection in climatology.…”
Section: Introductionmentioning
confidence: 99%
“…Op and TPW during the MJO event suggested that seasonal and interannual variability possibly have more dominant effects because of the geographic position and topographic condition (e.g., Kubota et al 2005Kubota et al , 2011.…”
mentioning
confidence: 99%